A Novel Method of Serum Resistance by Escherichia coli That Causes Urosepsis - Carrie F. Coggon (American Society for Microbiology, 2018)
ABSTRACT Uropathogenic Escherichia coli (UPEC) is the most common cause of urinary tract infection, which in some patients can develop into life-threatening urosepsis. Serum resistance is a key virulence trait of strains that cause urosepsis. Recently, we identified a novel method of serum resistance in patients with Pseudomonas aeruginosa lung infections, where patients possessed antibodies that inhibited complement-mediated killing (instead of protecting against infection). These inhibitory antibodies were of the IgG2 subtype, specific to the O-antigen component of lipopolysaccharide (LPS) and coated the bacterial surface, preventing bacterial lysis by complement. As this mechanism could apply to any Gram-negative bacterial infection, we hypothesized that inhibitory antibodies may represent an uncharacterized mechanism of serum resistance in UPEC. To test this, 45 urosepsis patients with paired blood culture UPEC isolates were screened for serum titers of IgG2 specific for their cognate strain’s LPS. Eleven patients had sufficiently high titers of the antibody to inhibit serum-mediated killing of UPEC isolates by pooled healthy control sera. Depletion of IgG or removal of O-antigen restored sensitivity of the isolates to the cognate patient serum. Importantly, the isolates from these 11 patients were more sensitive to killing by serum than isolates from patients with no inhibitory antibodies. This suggests the presence of inhibitory antibodies may have allowed these strains to infect the bloodstream. The high prevalence of patients with inhibitory antibodies (24%) suggests that this phenomenon is an important mechanism of UPEC serum resistance. LPS-specific inhibitory antibodies have now been identified against three Gram-negative pathogens that cause disparate diseases. IMPORTANCE Despite improvements in the early detection and management of sepsis, morbidity and mortality are still high. Infections of the urinary tract are one of the most frequent sources of sepsis with Escherichia coli the main causative agent. Serum resistance is vital for bacteria to infect the bloodstream. Here we report a novel method of serum resistance found in patients with UPEC-mediated sepsis. Antibodies in sera usually protect against infection, but here we found that 24% of patients expressed “inhibitory antibodies” capable of preventing serum-mediated killing of their infecting isolate. Our data suggest that these antibodies would allow otherwise serum-sensitive UPEC strains to cause sepsis. The high prevalence of patients with inhibitory antibodies in this cohort suggests that this is a widespread mechanism of resistance to complement-mediated killing in urosepsis patients, invoking the potential for the application of new methods to prevent and treat sepsis.